Comparison of the Bone Densitometry Results of Norland XR-36 and XR-46 Dual X Ray Absorptiometry (DXA) Scanners in the Rat Femurs - Koc, Zehra Pinar; Karayalcin, Binnur; Yildiz, Mustafa; Donmez, Baris Ozgur; Oguz, Nurettin; Oguz, Nurettin (Bentham Science Publ Ltd, 2015)
Background and objectives: It is important to obtain comparable results from different densitometry scanners in especially experimental studies. The aim of this experimental study in rat femurs is to compare bone densitometry results determined by two different DXA scanners of the same manufacturer performed at two different institutes. Materials and methods: Sixty female Wistar rats were the subject of this study. The rats were divided into four group and the groups were as follows: group 1 (n=15) (control), group 2 (n=15) (sham operated), group 3 (n=15) (ovariectomized) and group 4 (n=15) (ovariectomized and treated with losartan for eight weeks). Femurs of rats were collected and analyzed by Norland XR-36 and Norland XR-46 model DXA devices at different institutes by the same staff. In order to compare the two scanners results Paired samples T test, ANOVA and post hoc test was performed and p<0.05 considered significant. Results: The (bone mineral concentration) BMC and (bone mineral density) BMD results of two different scanners were not significantly different according to statistical analysis (p> 0.05) in the all 4 groups. Additionally BMD values were significantly decreased in group 3 compared to the control group (p<0,005). Although losartan treatment caused a significant increase in the BMD values of group 4 compared to the ovariectomy group (p<0.005) this increase could not reach the BMD values in the control group. Conclusions: Although it is important to use the same scanner for follow up DXA measurements in human, this experimental rat study shows that different scanners of the same manufacturer provides comparable results.
Keywords: Dual X-ray absorptiometry; repeatability; rats; osteoporosis